Peningkatan Daya Saing UMKM di Era New Normal Melalui Strategi Pembuatan Konten Promosi Digital - Mavilinda, Hera Febria; Nazaruddin, Akhmad; Daud, Islahuddin; Siregar, Muhammad Ichsan (Universitas katolik Musi Charitas, 2021)
In the New Normal Era, the use of social media digital platforms such as Instagram and Facebook is the right choice for Micro, Small and Medium Enterprises (MSMEs) to promotes their products. In order for MSMEs to be successful in promoting their products online, MSME need to design digital-based marketing strategies (Digital Marketing), including by creating digital promotional content. The problem that occurs today is the low ability of MSME in marketing their products on digital platforms. The lack of knowledge of MSME in creating digital promotional content is the cause of the low competitiveness of MSMEs in the context of digital marketing. This condition also occurs in MSMEs in Palembang City, where there are still many MSMEs in Palembang City who have not used digital platforms as online promotion media because of their limited knowledge and abilities. Referring to these conditions, this community service activity is carried out to provide education in the form of training to MSME on how to design strategies for creating digital promotional content. So it is hoped that through this training it can improve the ability of MSMEs in designing strategies for creating digital promotional content to attract consumer purchases and increase the volume of sales that have decreased due to the impact of the pandemic, as well as increase their competitiveness in maintaining business in the New Normal Era.